An evacuation system for extraordinary Indoor Air Pollution Disaster Circumstances - Karas, Ismail Rakip; Batuk, Fatmagul; Abdul-Rahman, Alias (DISASTER ADVANCES, 2012)
The problem of evacuating the buildings through the shortest path with safety has become more important than ever in a case of indoor air pollution incidents (i.e. fire, gas leak, airlessness, smother) taken place in complex and tall buildings of today's world. In this paper, it is aimed to present a 3D interactive human navigation, and evacuation system which generates an optimum path in 3D modeled buildings and provides 3D visualization and simulation. The system generates and transmits the guiding expression to the mobile devices such as PDA's, laptops etc. via internet. In order to evaluate its performance in a case of extraordinary indoor air pollution circumstance, the system was tested on a complex building model by using GPRS and WIFI internet connections based on the web technologies.
Keywords: Indoor pollution; indoor disaster; evacuation; network analysis; simulation; navigation; Geology; Meteorology & Atmospheric Sciences; Water Resources